Bandgap Engineering and Signature of Ferromagnetism in Ti1−xMnxO2 Diluted Magnetic Semiconductor Nanoparticles: A Valence Band Study. Issue 5 (25th January 2019) - Prajapati, Brijmohan; Roy, Somnath; Sharma, Subhash; Joshi, Amish G.; Chatterjee, S.; Ghosh, Anup K.
Abstract : Diluted magnetic semiconductor Ti1− x Mn x O2 (0.0 ≤ x ≤ 0.06) nanoparticles have been synthesized by sol–gel technique. Phase purity, structural, micro‐structural, and vibrational properties of the samples have been studied by X‐ray diffraction, transmission electron microscopy (TEM), high‐resolution TEM, and Raman spectroscopy. UV–Vis and photoluminescence spectroscopy clearly indicate the tuning of bandgap and appearance of different defect states (oxygen vacancies) with Mn‐doping, respectively. Chemical states and surface stoichiometry of the samples have been probed by X‐ray photoemission spectroscopy (XPS). Shifting of binding energy of Ti2p toward lower value and appearance of Mn 2+, Mn 3+, and Mn 4+ confirm Mn doping into TiO2 and also indicate that Mn‐doping reduces the number of oxygen vacancies in the system. Valence band studies have been done by XPS and ultraviolet photoemission spectroscopy (UPS) valence band spectra. Combined result of valence band spectra and optical data reveals shortening of HOMO–LUMO gap with increasing Mn‐concentration. Room temperature ferromagnetism, originating from oxygen vacancies, has been explained on the basis of the bound magnetic polaron (BMP) model. Resistivity measurements have been conducted to examine the semiconducting behavior and to study the electrical conduction mechanism. It is revealed that the thermally activated conduction (Arrhenius) mechanism is valid in the high temperature region whereas Mott's variable‐range hopping (VRH) mechanism is applicable in low temperature region. Abstract : Impact of the dopant on structural, optical, magnetic, and electronic properties of Mn‐doped TiO2 based diluted magnetic semiconductors has been reported. A decrease in inherent oxygen vacancies and a red shift of optical band gap with increasing doping concentration have been observed. The bound magnetic polaron model has successfully explained the observed ferromagnetism. Electronic studies reveal the samples retain the n‐type semiconducting behavior.